RETROSPECTIVE STUDY ON THE EVOLUTION OF TEETH WITH ENDODONTIC TREATMENT IN A GROUP OF PATIENTS FROM CRAIOVA - ROMANIA - Mihaela-Roxana Boțilă; Mihaela Jana Țuculina; Oana Andreea Diaconu; Mihaela Ionescu; Petre Costin Mărășescu; Luana Corina Lascu; Veronica Mercuț (Romanian Society of Oral Rehabilitation, 2024)
The importance of preserving dental tissues together with the evolution of dental techniques and materials has led to advances in the field of endodontics and new principles in tooth restoration. Endodontically treated teeth are more prone to fracture and endodontically treated abutment teeth have a lower survival rate compared to vital abutment teeth. The aim of this study was to establish the evolution of teeth with endodontic treatment in a group of patients from Craiova, the frequency of various forms of failure of endodontic treatment and to identify the factors that contributed to the failure or success of endodontic treatment. Materials and Methods: This study was carried out based on the clinical and radiological examination and the consultation of the treatment sheets of some patients who came for treatment in the Dental Prosthetics Clinic of the Faculty of Dental Medicine of the University of Medicine and Pharmacy Craiova. The general technical quality of the endodontic treatment was evaluated based on the guidelines published by the European Society of Endodontology, following the radiological appearance of the root canal obturation as well as the presence of periapical lesions. The periapical index (PAI) proposed by Orstavik et al. was used to assess the periapical condition of teeth with root canal fillings. Results: The most common indications for endodontic treatment were irreversible pulpitis (64.05%) and endodontic treatment for prosthetic purposes (23.72%). Periapical lesions were observed in 33.4% of all endodontically treated teeth. Periapical lesions were observed in 35.2% of endodontically treated abutment teeth compared to 7.1% of vital abutment teeth. Conclusions: The most common indications for endodontic treatment were irreversible pulpitis and endodontic treatment for prosthetic purposes. Endodontic treatments for prosthetic purpose were very frequent although there are clear recommendations against it. Periapical complications were recorded in a higher proportion in case of abutment teeth.